Producción de plántulas de café (coffe arabica L.) de buena calidad en fase de semillero - Pambi Lalagui, Cristina Elizabeth (2018)
This search was carried out in the Carmelo neighborhood, Cangonamá parish, Paltas canton, Loja province, the objective was to determine the method of planting coffee in the seedbed that accelerates the emergence and release of cotyledons and evaluate three disinfectants, The uniformity and vigor of the plants. The methods used were seed with parchment, seed without parchment and seed without parchment pre-germinated; These seeds were sown in previously disinfected sand with boiled water, ash + soap and pepper extract. The variables to be evaluated were percentage of emergence, days at the opening of cotyledons, height, root length, stem diameter, cotyledon surface, shoot dry mass and root. The emergency evaluation was performed from the moment the first seeds emerged, 42 days after sowing in seeds with parchment and without parchment and at 22 days in seeds without pre-germinated parchment. Cotyledon opening was evaluated after emergence at 48 days in seeds with parchment, 32 days in seeds without parchment and in seeds without pre-germinated parchment. At the end of the experimental trial, dry mass of shoot and root, total dry mass, root length were evaluated. The best results for emergence with more than 80% were boiled water seed plus parchment (T1), pre-germinated seed (T3), cotyledon opening of the nine treatments ash seedlings + soap Seed without parchment (T5), and pre-germinated seed (T6) showed results lower than 80%; In height, stem diameter, dry mass of shoot, total dry mass, root length seeded boiled water plus seed with parchment (T1) had better results, seedbed with boiled water plus seed with parchment (T1 ) And seed without parchment (T2) presented better leaf area, the best treatment of the dry mass was the boiled water seed plus seed without parchment (T2) and chilli plus seed with parchment (T7) and seedlings that had a value Lower in terms of ICD were the ash seed + soap and pre-germinated seed (T6) and chilli plus pre-germinated seed (T9). Key words: seed, disinfectan